SOCIAL MEDIA AS THE HEGEMONIC ARENA OF K-POP: THE ROLE OF CONTENT AND TECHNOLOGICAL INNOVATION IN SHAPING FANDOM - Kumi Laila; Faikoh Umairoh (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
Social media has evolved into a key space for creating and strengthening the global dominance of K-Pop culture. This study examines the role of digital content and technology innovation in strengthening K-Pop's influence through active engagement between the entertainment industry, digital platforms, and fans. By utilizing algorithms from platforms such as YouTube, TikTok, Instagram, X (Twitter), and digital media such as Weverse and bubble, the K-Pop industry not only distributes content widely but also builds a participatory ecosystem that encourages fans to engage in the process of content production, distribution, and promotion. This phenomenon shows that fans are no longer passive but have become a key element in expanding the influence of K-Pop culture through practices such as fanbase organization, fan translations, and viral challenges. This study uses a qualitative descriptive approach and digital ethnography to analyze K-Pop's dominance on social media, identify the role of content in shaping fandom, and examine the impact of technology on fan interactions. The research findings indicate that K-Pop's dominance on social media is not only built on the quality of cultural products, but also through the use of digital technology that supports content personalization, accelerated information dissemination, and the formation of collective identity among fans. Thus, social media acts as a complex hegemonic space, a place where cultural power is negotiated between producers and consumers in the evolving digital ecosystem.